2021
DOI: 10.1016/j.ekir.2020.11.021
|View full text |Cite|
|
Sign up to set email alerts
|

Low Serum Potassium Levels and Clinical Outcomes in Peritoneal Dialysis—International Results from PDOPPS

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 32 publications
1
40
0
4
Order By: Relevance
“…It has been reported that hypokalemia tightly correlates with peritonitis, 4,15,16,18 we next analysed the relationships of peritonitis with LK and SLK. During a total of 17,840 months of PD vintages in 602 patients, 153 patients occurred peritonitis with 230 episodes.…”
Section: Relationship Between Peritonitis and Hypokalemiamentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that hypokalemia tightly correlates with peritonitis, 4,15,16,18 we next analysed the relationships of peritonitis with LK and SLK. During a total of 17,840 months of PD vintages in 602 patients, 153 patients occurred peritonitis with 230 episodes.…”
Section: Relationship Between Peritonitis and Hypokalemiamentioning
confidence: 99%
“…A large number of studies have shown the relationships between hypokalemia and some serious clinical complications, including malnutrition, 26 arrhythmia, 11 cardiac arrest, 12 and overall mortality, 3,13 as well as peritonitis. 4,16,18 When the SK level decreased to less than 3.5mEq/L, the incidence of peritonitis greatly increased, with an HR of 1.15-1.56. 18,24 While, to our knowledge, there were few reports about the relationship of peritonitis and serious hypokalemia (SK level <3.0 mEq/L).…”
Section: Ta B L Ementioning
confidence: 99%
See 3 more Smart Citations